PENGARUH TINGKAT KEBISINGAN AKIBAT LALU LINTAS PESAWAT DI BANDARA SYAMSUDIN NOOR TERHADAP KOMUNIKASI MASYARAKAT DI KELURAHAN SYAMSUDIN NOOR KELURAHAN GUNTUNG PAYUNG DAN KELURAHAN LANDASAN ULIN TIMUR - M Nur Taufiqurrahman; Deasy Arisanty; Karunia Puji Hastuti (JPG (Jurnal Pendidikan Geografi), 2015)
The title of research is “the level of noise due to air traffic at syamsudin noor airport, against public communication in the Syamsudin Noor village, Guntung Payung village, and east Landasan Ulin village”. The purpose of research was to determine noise value and public response to communication disarders due to air traffic at Syamsudin Noor airport.The populations of this research are community in the Syamsudin Noor village, Guntung Payung village, and east Landasan Ulin village. Technique sampling used is area sampling /cluster sampling. Sample of this research are 47 (68%) man and 22 (32%) women in the Syamsudin Noor village, Guntung Payung village, and east Landasan Ulin village, living just under the air traffic that area measured from zero point, which is the area oustside of fence airport 500 meters. Including the below quality standartd limits of noise level KEP-8/MENLH/11/1996 for settlement by 55 dB(A) and measured ±50 meters per radius from zero pint. Data collection techniques in this research used quantitative descriptive analysis as well as finding a relstionship between two variables with product moment correlation method.The results of each point correlation research based on calculations using application spss 16 and the equation correlation pearson shows that a significant relation exists in the south at the airport Syamsudin Noor, this is a result of the south the airport syamsudin noor there are a main road traffic motor vehicles which are dense enough crosswalk because it is road linking has among cities, so that an impact add loud noise level in the area Key word: noise, communication disorders, public